Techno-economic assessment of a Synechocystis based biorefinery through process optimization - A. Ferreira da Silva; C. Brazinha; L. Costa; N. S. Caetano (Energy Reports, 2020)
Similar to oil, biological origin feedstock can be converted into a number of products allowing to recover the maximum value from the raw biological material, within what is nowadays called a biorefinery. Among other biological materials, microalgae are a very interesting biomass due to the high economic value of certain cellular components, such as carotenoids and polyunsaturated fatty acids. In this project, a genetically modified cyanobacteria, that produces ethanol as an extracellular product, was used as the basis of this study. In order to assess the optimal configuration of the biorefinery, different scenarios were designed, each one with different sequences of unit operations, equipment and products. With the design stage completed, an economic analysis was performed to choose the 2 scenarios with the best economic performance.
Keywords: 330; LCA; Microalgae biorefinery; Process optimization; Sustainability evaluation